Inulin impacts tumorigenesis promotion by colibactin-producing Escherichia coli in ApcMin/+ mice - Oliero, Manon; Hajjar, Roy; Cuisiniere, Thibault; Fragoso, Gabriela; Calvé, Annie; Santos, Manuela M. (Frontiers in Microbiology, 2023)
The prebiotic inulin has previously shown both protective and tumor-promoting effects in colorectal cancer (CRC). These inconsistencies may be due to the gut microbial composition as several bacteria have been associated with CRC. Specifically, polyketide synthase-positive (pks+) Escherichia coli promotes carcinogenesis and facilitates CRC progression through the production of colibactin, a genotoxin that induces double-strand DNA breaks (DSBs). We investigated whether colibactin-producing E. coli changed the protection conferred by inulin against tumor growth and progression using the ApcMin/+ mouse model of CRC. Mice received a 2% dextran sodium sulfate (DSS) solution followed by oral gavage with the murine pks+ E. coli strain NC101 (EcNC101) and were fed a diet supplemented with 10% cellulose as control or 10% inulin for four weeks. Inulin supplementation led to increase EcNC101 colonization compared to mice receiving the control diet. The increased colonization of EcNC101 resulted in more DSBs, tumor burden, and tumor progression in ApcMin/+ mice. The tumorigenic effect of EcN101 in ApcMin/+ mice mediated by inulin was dependent on colibactin production. Pasteurized E. coli Nissle 1917 (EcN), a probiotic, suppressed the inulin-driven EcNC101 expansion and impacted tumor progression. Our results suggest that the presence of pks+ E. coli influences the outcome of inulin supplementation in CRC and that microbiota-targeted interventions may mitigate this effect. Given the prevalence of pks+ E. coli in both healthy and CRC populations and the importance of a fiber-rich diet, inulin supplementation in individuals colonized with pks+ bacteria should be considered with caution.